Ziyad-oglu Qacarlar and Karabakh Province Foundation in 16 Century - A. G. Nesterov; M. I. Qacar (Научный диалог)
The history of formation of Ganja-Karabakh Province of Safavid Empire is shown and the role of the tribal unions of Qajar in this process is examined. The article shows the activities of Qajars political leaders of that time - Kamal ad-Din Khan and Imamkuli Khan, their participation in the hostilities that led the rulers of the Safavid Empire in the South Caucasus, as well as participation of the Qajars in the hostilities of the Ottoman-Safavid war of the 16th century. Based on the analysis of historical sources, it is shown that it was the Qajar leaders who played a leading role in the spread and preservation of Safavid power in the territories of the South Caucasus, including the lands of Shirvan and Georgian States. It is shown that under the influence of the Qajars there were territories located at the junction of the borders of modern Georgia and Azerbaijan - Shamshadil, Borchalu and Kazakh possessions, control over which was essential for the entire communication system of the South Caucasus. The paper also examines in detail the origin and early history of Ziyad-oglu Qacarlar - a dynastic branch whose descendants ruled the Karabakh Khanate from the middle of the 18th century until the region’s accession to the Russian Empire.